HISTORY AND EVOLUTION, TYPES OF DICTIONARIES - Tursunova Zulxumor Safali qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This article examines the origin and historical development of dictionaries, as well as the main types of English dictionaries, their structure, purpose, and areas of use. Dictionaries serve as an essential tool for language learners, teachers, translators, and writers by providing information on word meanings, pronunciation, grammar, and usage. The article categorizes English dictionaries into monolingual, bilingual, learner’s, specialized, and historical types. Each type performs its own specific function and meets the diverse needs of users. The article also briefly discusses the evolution of dictionaries and the role of digital formats in language learning.